Cervical Cerclage vs. Pessary in Women with a Short Cervix on Ultrasound - Pergialiotis, Vasilios; Psarris, Alexandros; Antsaklis, Panagiotis; Theodora, Marianna; Papapanagiotou, Aggeliki; Rodolakis, Alexandros; Daskalakis, Georgios (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Purpose In the present study we sought to compare the efficacy of cervical pessary to that of cerclage in terms of reducing preterm birth rates among women with a short (<25 mm) or ultra-short (<15 and <10 mm) cervix during the ultrasonographic second-trimester assessment.Method We retrospectively searched the hospital records for singleton pregnancies diagnosed with cervical insufficiency during the second trimester of pregnancy. The McDonald cerclage using a 5mm Mersilene tape was used in all women. An Arabin pessary was used uniformly. In all cases 80 mg of vaginal progesterone gel were administered daily until 37 weeks of gestation.Results Overall, 294 women (124 (42.2%) with a McDonald cerclage and 170 (57.8%) with placement of an Arabin pessary) were selected for analysis. Preterm birth rates <37 weeks were similar in both groups (C: 30/122 vs. P: 35:165, p=.581) as well as PTB <34 weeks (C: 16/122 vs. 15/150, p=.278). Admission to the NICU and need for CPAP were more prevalent in the cerclage group (p<.001). Analysis of cases with a cervix <15 mm and <10 mm indicated that preterm birth rates remained equal among the groups, while an increased risk of NICU admission was seen in cases with a cervical length <10 mm that were treated with cerclage.Discussion and Conclusion Cervical pessary may be an alternative to cervical cerclage for women with second-trimester cervical shortening and its effect may persist even among cases with an ultra-short cervix. Future randomized trials are needed to ascertain these findings.
Keywords: pessary; preterm birth; cervical insufficiency; Arabin; cervical length